PENENTUAN SEBARAN SPASIAL PENCEMARAN AIR DI KOTA PONTIANAK MENGGUNAKAN ANALISIS DISKRIMINAN DUA KELOMPOK - Muhammad Fikri; Naomi Nessyana Debataraja; Dadan Kusnandar (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2019)
Clean water is one point of sustainable Development Goals (SDGs), so to keep indicator water quality must be determine every period. The Discriminant analysis is an analysis of dependence that is used to classify objects into several categories. The purpose of this study were to determine the discriminant model that consist of dominant factors of water pollution. Samples were taken from 42 locations in the surrounding area of Pontianak City. The sample were analyzed in the laboratory for the contents of ferrum (Fe), dissolved oxygen (DO), biochemical oxygen demand (BOD). Width of the river were also considered is an independent variable. The methodology includes determining the pollution index that will be used as dependent variable, testing the assumption of multivariate normality and similarity of the covariance variance, conducting the discriminant analysis classification process using the Apparent Error Rate method. The pollution level of each location was visualized in a map. The resulting discriminant model has an accuracy rate of 69%.